MANAJEMEN LEMBAGA PENDIDIKAN ISLAM DI INDONESIA - Khairul, Agus; Jazuli, Jazuli (Jurnal Ilmiah Pendidikan dan Keislaman, 2022)
Management of Islamic education, may be a word that we often know, we hear even we do, but many of us may not fully understand the meaning of the definition of islamic education management. Therefore we must see what exactly the meaning or definition of the management of Islamic educational institutions. There are various opinions that suggest about the definition of Islamic education management, therefore we need an agreement in advance what is meant by islamic education management. The development of an institution is very dependent on the management process or / management. If the management is good the institution will also develop well and vice versa. Management is a process to achieve organizational objectives by carrying out activities of 4 main functions, namely Planning, organizing, actuating, and controlling. Thus, management is an ongoing activity. These management functions interact with each other and hook each other up, resulting in a so-called management process. Thus, the management process is actually a process of interaction between various management functions